1977
DOI: 10.1080/00288330.1977.9515709
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and nitrate run‐off in hill pasture and forest catchments, Taita, New Zealand

Abstract: Phosphorus and nitrogen were measured in stream run-off from the four catchments of the Taita Experimental Basin (41° 11´ S, 174° 58´ E). The land is used as exotic conifer forest, native forest, and hill pasture. Multiple regression analysis was used to estimate chemical losses per unit area in floods and at low flows.At low flows, the hill pasture (fertilised with lime at 630 kg·ba -1 ·y -1 , and superphosphate at 380 kg·ha -1 ·y -1 ) tended to lose more phosphorus and nitrate than the forested land, but dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
4

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 11 publications
0
13
4
Order By: Relevance
“…Overall P losses were low compared with results of P transfer from grazed land in Europe (Haygarth and Jarvis, 1997) and New Zealand (McColl et al, 1977). Values found in the present study are lower than those for P transfer found in forestry catchments in Chile (650 g ha -1 yr -1 ; Oyarzun et al, 1997).…”
Section: Phosphorus Lossescontrasting
confidence: 71%
See 1 more Smart Citation
“…Overall P losses were low compared with results of P transfer from grazed land in Europe (Haygarth and Jarvis, 1997) and New Zealand (McColl et al, 1977). Values found in the present study are lower than those for P transfer found in forestry catchments in Chile (650 g ha -1 yr -1 ; Oyarzun et al, 1997).…”
Section: Phosphorus Lossescontrasting
confidence: 71%
“…Peaks of RP concentration were measured associated to spring P fertilizer application during all years and were greater than those reported by McColl et al (1977) for grasslands on volcanic soils. The high RP concentrations after TSF addition was probably due to the direct transport of fertilizers granules in runoff after the application and because TSP granules were rapidly solubilized by surface runoff (Heathwaite et al, 1998).…”
Section: Phosphorus Lossescontrasting
confidence: 56%
“…Peaks of TP and RP concentrations in run‐off were associated with spring P fertilizer application during both years and were greater than those reported by McColl et al. (1977) for grasslands on volcanic soils.…”
Section: Discussioncontrasting
confidence: 55%
“…It is defined as the fraction of TP exported from the landscape to the rivers as DIP. Plotlevel and regional studies have generally found that about 0.1-3.3% of the P applied as fertilizer or manure was lost as DIP via surface runoff transport (Burwell et al 1997;McColl et al 1977;Nicholaichuk and Read 1978;Sharpley and Syers 1979;McDowell and McGregor 1984;Sharpley et al 1995;Bennett et al 1999;Baker and Richards 2002;Cao and Lin 2006). However, Harrison et al (2005) believed that the fractional loss as DIP was underestimated in watersheds with high runoff; therefore, they allowed the fraction to vary between 1 and 10%.…”
Section: Watershed Exportmentioning
confidence: 99%